1986
DOI: 10.1128/aem.52.3.450-459.1986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inactivation of enteric viruses in fresh water

Abstract: Fresh water obtained from nine sources was shown to cause inactivation of poliovirus. Further testing with four of these water samples showed that enteric viruses from different genera were consistently inactivated in these freshwater samples. Studies on the cause of inactivation were conducted with echovirus type 12 as the model virus. The results revealed that the virucidal agents in the waters tested could not be separated from microorganisms. Any treatment that removed or inactivated microorganisms caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
50
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 23 publications
4
50
1
Order By: Relevance
“…Discrepancies in inactivation kinetics in sterilized and nonsterilized wastewater have been reported previously for nonenveloped viruses, 46 and may be due to bacterial extracellular enzyme activity and protozoan or metazoan predation. 47,48 Overall, the results suggest that unpasteurized wastewater samples should be employed for survivability tests when feasible.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…Discrepancies in inactivation kinetics in sterilized and nonsterilized wastewater have been reported previously for nonenveloped viruses, 46 and may be due to bacterial extracellular enzyme activity and protozoan or metazoan predation. 47,48 Overall, the results suggest that unpasteurized wastewater samples should be employed for survivability tests when feasible.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…Water type was also a significant predictor of the rate of viral reduction, with greater reduction in pasteurized settled sewage as compared to reagent-grade water. Factors that have been suggested as contributors to greater virus reduction in more contaminated water include pH extremes, the presence of other microorganisms, and certain chemical constituents, such as proteolytic enzymes (Ward et al, 1986). However, the pasteurization process used to inactivate vegetative bacteria in the pasteurized settled sewage in these experiments may have reduced proteolytic activity in the test water.…”
Section: Discussionmentioning
confidence: 98%
“…Although the conditions of these experiments may differ from the natural environment, the present experiments indicated that reos and polios are capable of surviving for a very long time in river water. As to the survival time of viruses in water, effects of many factors such as water quality, temperature, light, enzymes derived from microorganisms, and turbidity have to be taken into consideration (2,16,19,22,23). It has been reported that water temperature is the most dominant factor among them.…”
Section: Discussionmentioning
confidence: 99%